Pemberdayaan Masyarakat Melalui Penanaman Berkelanjutan Berbasis PAR di Desa Hariang - Susilawati; Unang Ruhyat; Acep Abdul Rismana; Ainun Nisha; Nema (IKHTIAR: Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service Program aims to empower the community of Hariang Village, Buahdua District, Sumedang Regency through a sustainable planting program using the Participatory Action Research (PAR) approach. The main issue addressed is the underutilization of productive land and the low awareness of sustainable agricultural practices that support long-term economic development. Community empowerment is positioned as a participatory process in which local residents are actively involved in all program stages. The PAR method was implemented to encourage community participation in problem identification, planning, implementation, and evaluation. Activities included planting white teak and durian trees, as well as cultivating corn and chili in collaboration with local residents, the Women Farmers Group, and village authorities. Data were collected through observation, participation, and documentation. The results indicate increased community participation and awareness of sustainable agriculture. The community also showed improved motivation to manage productive land more effectively. Furthermore, these activities demonstrate potential economic benefits that may contribute to community income in both the short and long term. This program shows that PAR-based sustainable planting can be an effective model for community development focused on environmental sustainability and economic self-reliance.